2018
DOI: 10.1186/s13041-018-0373-8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic overexpression of SQSTM1/p62 accelerates disease onset in a SOD1H46R-expressing ALS mouse model

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by a selective loss of upper and lower motor neurons. Recent studies have shown that mutations in SQSTM1 are linked to ALS. SQSTM1 encodes SQSTM1/p62 that regulates not only autophagy via the association with MAP1LC3/LC3 and ubiquitinated proteins but also the KEAP1-NFE2L2/Nrf2 anti-oxidative stress pathway by interacting with KEAP1. Previously, we have demonstrated that loss of SQSTM1 exacerbates disease phenotypes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
(62 reference statements)
2
28
0
1
Order By: Relevance
“…However, many mouse models exist that demonstrate a relationship between p62 and other ALS genes. Mitsui et al (2018) previously reported that loss of SQSTM1 exacerbates disease phenotypes in SOD1H46R ALS mice. Following the initial report, the same authors demonstrated that SQSTM1 overexpression results in a significant increase in biochemically detectable insoluble SQSTM1 and poly-ubiquitinated proteins in the spinal cord of SQSTM1; SOD1H46R mice when compared to SOD1H46R mice.…”
Section: Sequestosome-1 (Sqstm1)mentioning
confidence: 93%
See 1 more Smart Citation
“…However, many mouse models exist that demonstrate a relationship between p62 and other ALS genes. Mitsui et al (2018) previously reported that loss of SQSTM1 exacerbates disease phenotypes in SOD1H46R ALS mice. Following the initial report, the same authors demonstrated that SQSTM1 overexpression results in a significant increase in biochemically detectable insoluble SQSTM1 and poly-ubiquitinated proteins in the spinal cord of SQSTM1; SOD1H46R mice when compared to SOD1H46R mice.…”
Section: Sequestosome-1 (Sqstm1)mentioning
confidence: 93%
“…Following the initial report, the same authors demonstrated that SQSTM1 overexpression results in a significant increase in biochemically detectable insoluble SQSTM1 and poly-ubiquitinated proteins in the spinal cord of SQSTM1; SOD1H46R mice when compared to SOD1H46R mice. This observation suggests that overexpression of p62 in SOD1H46R mice accelerates disease onset by impairing the protein degradation pathways (Mitsui et al, 2018).…”
Section: Sequestosome-1 (Sqstm1)mentioning
confidence: 95%
“…8,31 Owing to its role in protein degradation, overexpression of p62 has been shown to be protective in some neurodegenerative animal models, but overexpression in a SOD1 ALS model was found to accelerate disease onset. [32][33][34] Taken together, these studies suggest that a fine balance in p62 levels is required for optimal signaling and protein clearance. Consequently, small changes in Abbreviations: ALS = amyotrophic lateral sclerosis; fALS = familial ALS; I/D = insertion/deletion; sALS = sporadic ALS; SQSTM1 = sequestosome 1. a Each row compared using random effects to account for familial correlation.…”
Section: Discussionmentioning
confidence: 85%
“…E3 ubiquitin ligases, for example, have been linked to a wide range of neurodegenerative diseases; for a thorough review see George et al (2018). Alterations to protein degradation have been implicated in a broad spectrum of neurodegenerative conditions including PD, HD, Multiple Sclerosis and ALS (Mitra et al, 2009;Koch et al, 2015;Albert et al, 2017;Mitsui et al, 2018). UPS and autophagy have become increasingly pursued areas of study in conjunction with neurodegenerative and protein aggregation diseases (George et al, 2018;Kabir et al, 2020;Kumar et al, 2020;Lambert-Smith et al, 2020;Lim et al, 2020;Papanikolopoulou and Skoulakis, 2020;Tundo et al, 2020).…”
Section: Protein Degradation and Diseasementioning
confidence: 99%